Mating with dead conspecifics in an invasive ladybird is affected by male sexual fasting and time since the female’s death - Řeřicha, Michal; Montoya-Molina, Santiago; Harabiš, Filip; Knapp, Michal (Frontiers in Ecology and Evolution, 2023)
High promiscuity and low mating partner choosiness in insects can sometimes result in a deviated mating behaviour such as mating with already dead individuals. In this study we investigated the occurrence of necrophilic behaviour in males of the invasive ladybird Harmonia axyridis using two laboratory experiments. For both no-choice and choice experiments, the probability of mating and mating duration were significantly affected by female status (alive, 1-day, 7-day, or 14-day old carcass) and by male mating status (unmated or mated) which was investigated in the no-choice experiment. The presence of chemical cues produced by an alive female did not affect the probability of a male mating with a dead female.In the no-choice experiment, 14-day old female carcasses were significantly less attractive than alive females, and unmated males tended to mate with females of all statuses with significantly higher probability than mated males. In the choice experiment, males showed a significant preference to mate with alive females when compared to 7-day old carcasses but did not distinguish between alive females and 1-day old carcasses. Mating latency (time to the starting of mating) tended to be longer for 14-day old carcasses in the no-choice experiment and was not affected by female status in the choice experiment. Mating duration was negatively affected by age of female carcasses in the no-choice experiment and only 7-day old carcasses were mated for significantly shorter time than alive females in the choice experiment. Mating behaviour was highly consistent for the no-choice and choice experiments. Despite decreasing probability of mating with 7-day and 14-day old carcasses, we observed a surprisingly high frequency of mating with dead conspecifics in the invasive ladybird Harmonia axyridis, which could have serious consequences for transmission of pathogens and affect male fitness even under natural conditions.